Evaluating the Impact of the Long-S upon 18th-century Encyclopedia Britannica Automatic Subject Metadata Generation Results. - Grabus, Sam (Information Technology & Libraries, 2020)
This research compares automatic subject metadata generation when the pre-1800s Long-S character is corrected to a standard < s >. The test environment includes entries from the third edition of the Encyclopedia Britannica, and the HIVE automatic subject indexing tool. A comparative study of metadata generated before and after correction of the Long-S demonstrated an average of 26.51 percent potentially relevant terms per entry omitted from results if the Long-S is not corrected. Results confirm that correcting the Long-S increases the availability of terms that can be used for creating quality metadata records. A relationship is also demonstrated between shorter entries and an increase in omitted terms when the Long-S is not corrected.